Functional and molecular characterization of the Atlantic salmon gill epithelium cell line ASG-10; a tool for in vitro gill research - Slattery, Orla; Dahle, Maria K.; Sundaram, Arvind Y. M.; Nowak, Barbara F.; Gjessing, Mona C.; Solhaug, Anita (Frontiers in Molecular Biosciences, 2023)
Fish gills are not only the respiratory organ, but also essential for ion-regulation, acid-base control, detoxification, waste excretion and host defense. Multifactorial gill diseases are common in farmed Atlantic salmon, and still poorly understood. Understanding gill pathophysiology is of paramount importance, but the sacrifice of large numbers of experimental animals for this purpose should be avoided. Therefore, in vitro models, such as cell lines, are urgently required to replace fish trials. An Atlantic salmon gill epithelial cell line, ASG-10, was established at the Norwegian Veterinary institute in 2018. This cell line forms a monolayer expressing cytokeratin, e-cadherin and desmosomes, hallmarks of a functional epithelial barrier. To determine the value of ASG-10 for comparative studies of gill functions, the characterization of ASG-10 was taken one step further by performing functional assays and comparing the cell proteome and transcriptome with those of gills from juvenile freshwater Atlantic salmon. The ASG-10 cell line appear to be a homogenous cell line consisting of epithelial cells, which express tight junction proteins. We demonstrated that ASG-10 forms a barrier, both alone and in co-culture with the Atlantic salmon gill fibroblast cell line ASG-13. ASG-10 cells can phagocytose and express several ABC transport proteins. Additionally, ASG-10 expresses genes involved in biotransformation of xenobiotics and immune responses. Taken together, this study provides an overview of functions that can be studied using ASG-10, which will be an important contribution to in vitro gill epithelial research of Atlantic salmon.